Rare head and neck cancers and pathological diagnosis challenges – A systematic review. - Shunmugavelu, Dr. Karthik; Devendran, Dr. Hemalatha; Shanmugam (Student's Journal of Health Research Africa, 2026)
Background Rare head and neck cancers present substantial diagnostic challenges due to overlapping histopathological features, complex molecular profiles, and clinical heterogeneity. Distinguishing metastatic disease, second primaries, and uncommon histological variants requires integration of qualitative pathological assessment and quantitative radiological evaluation. Advanced molecular tools, including next-generation sequencing and molecular classifier assays, are increasingly incorporated to improve diagnostic precision and therapeutic stratification. Material and methods A systematic review was conducted in accordance with PRISMA guidelines. Electronic databases including PubMed, MEDLINE, Scopus, Embase, Web of Science, and LILACS were searched for studies published between 2020 and 2024. Eligibility criteria included original research articles, case studies, and systematic investigations addressing rare head and neck cancers and associated diagnostic challenges. Studies unrelated to diagnostic methodology or not focused on rare entities were excluded. Extracted data items included author, year, country, study design, diagnostic modality, and clinical outcome relevance. Study quality was assessed using the STROBE checklist where applicable. Results Seven eligible studies were included. Findings demonstrated that qualitative histopathological diagnosis remains central to treatment planning but is limited by interobserver variability and tumor heterogeneity. Quantitative imaging modalities such as CT, MRI, and PET improved tumor localization and staging accuracy. Molecular profiling, biomarker identification, and gene expression assays enhanced primary site identification and prognostic assessment, particularly in cancers of unknown primary and salivary gland malignancies. Multidisciplinary tumor board discussions were consistently associated with optimized therapeutic decision-making and improved care coordination. Conclusion Accurate diagnosis of rare head and neck cancers requires integration of specialized pathological expertise, advanced molecular diagnostics, and structured multidisciplinary evaluation to guide individualized treatment strategies and improve clinical outcomes. Future research Collaborative international consortia will be necessary to generate adequately powered datasets for these uncommon tumors